Head, trunk and arm posture amplitude and variation, muscle activity, sedentariness and physical activity of 3 to 5 year-old children during tablet computer use compared to television watching and toy play - Howie, Erin; Coenen, P.; Campbell, A.; Ranelli, S.; Straker, Leon (Elsevier, 2017)
Young children (ages 3 to 5) are using mobile touchscreen technology, including tablet computers, yet little is known on the potential musculoskeletal and physical activity implications of its use. This within-subject laboratory study (n = 10) examined head, trunk and arm postures, upper trapezius muscle activity, and total body and upper limb physical activity during playing with tablets compared to during TV watching and playing with non-screen toys. Overall, this study found that during tablet play children had greater mean head, trunk and upper arm angles compared to both TV watching and toy play. Conversely, compared to toy play, children playing with tablets had lesser trunk, upper arm and elbow postural variation, lesser trapezius activity, more time sitting and lesser physical activity. Thus, to minimize potential musculoskeletal and sedentary risks, non-screen toy play should be encouraged and education and guidelines provided for parents and caretakers to support wise use of tablets.